PHOTOCATALYTIC DEGRADATION OF PHARMACEUTICAL DRUG ZIDOVUDINE BY UNDOPED AND 5 % BARIUM DOPED ZINC OXIDE NANOPARTICLES DURING WATER TREATMENT: SYNTHESIS AND CHARACTERISATION - Bhamare, Vijaykumar S.; Kulkarni, Raviraj M. (International Journal of Applied Pharmaceutics, 2019)
Objective: To study the photocatalytic degradation of pharmaceutical drug zidovudine (ZDV) by synthesized undoped zinc oxide nanoparticles (ZONPs) and 5% (mole ratio) barium doped zinc oxide nanoparticles (BZONPs) during water treatment. Methods: Kinetics studies were carried out with the help of UV-Visible Spectrophotometer. High-Resolution Mass Spectrophotometry (HR-MS) was used to identify products. A photo-reactor with mercury lamp was used as an external source of light energy. Optical power meter was used for the measurement of light intensity. The particle size of the synthesized photocatalysts was identified with the help of siemens x-ray diffractometer (XRD). The surface topography of photocatalysts was done by scanning electron microscope (SEM). Transmission electron microscopy (TEM) was used for the studies of particle size and morphology. Results: Five degraded products of ZDV are identified by HR-MS. A suitable electron-hole pair mechanism is projected. XRD patterns show that the intensity of peak is slightly stronger in ZONPs. There is an increase in the rate of photocatalytic degradation of ZDV by adding different quantities of photocatalyst from 0.05 g l-1 to 0.1 g l-1. The kinetic data reveals that there is an initial increase in the values of rate constants with the increase in the concentration of ZDV. The kinetic data indicate that the values of rate constants are higher at pH = 9. There is an increase in the rate constant values with an increase in the light intensities of UV lamp. Conclusion: The rates of photocatalytic degradation of ZDV were found to be higher using 5 % (mole ratio) BZONPs as a photocatalyst. Â